UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I MENGGUNAKAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) BERBANTUAN GAME EDUKATIF WORDWALL - Ziazatul Haq, Arina; Pamujo, Pamujo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of beginning reading ability among first-grade students at SDN 01 Karangnangka, Purbalingga Regency, Central Java Province, served as the basis for conducting this study. Of the 19 students in the class, many still experienced difficulties in beginning reading. This study aimed to improve the beginning reading skills of first-grade students at SDN 01 Karangnangka, both in terms of the learning process and learning outcomes, through the use of the Structural Analytic Synthetic (SAS) method assisted by the Wordwall educational game. This research employed Classroom Action Research consisting of two cycles, with each cycle involving planning, action implementation, observation, and reflection stages. The subjects of this study were 19 first-grade students at SDN 01 Karangnangka. The results showed that the implementation of the Structural Analytic Synthetic (SAS) method, supported by the Wordwall educational game, was able to improve both the quality of the learning process and the beginning reading ability of first-grade students at SDN 1 Karangnangka. This improvement could be seen from the average scores of beginning reading skills and the percentage of students achieving learning mastery. In Cycle I, the average beginning reading score was 85, with a learning mastery percentage of 63%. Furthermore, in Cycle II, the average score increased to 92, with a learning mastery percentage of 84%.